2007
DOI: 10.1590/s0100-879x2006005000112
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in genes MTHFR, MTR and MTRR are not risk factors for cleft lip/palate in South Brazil

Abstract: Non-syndromic cleft lip and palate (CL/P) occurs due to interaction between genetic and environmental factors. Abnormalities in homocysteine metabolism may play a role in its etiology due to polymorphisms in genes involved in this pathway. Because of the involvement of MTHFR, MTR and MTRR genes with folate metabolism and the evidence that maternal use of folic acid in early pregnancy reduces the risk for CL/P, we evaluated the influence of their polymorphisms on the etiology of CL/P through a case-control stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 26 publications
(18 reference statements)
2
30
1
7
Order By: Relevance
“…Other folates and NTD-related genes, such as methylenetetra-hydrofolate dehydrogenase (MTHFD), have not been evaluated in Brazilian population yet. Brazilian antecedents on the prevalence of the 677C>T mutation came from different populations and ethnic groups and in general, they indicated a prevalence below 10 % of TT homozygous individuals and higher prevalence of the mutation in individuals with European than African or Amerindian ancestry (Ferreira-Fernandes et al 2013;Franco et al 1998;Brandalize et al 2007;Arruda et al 1998). …”
Section: Discussionmentioning
confidence: 99%
“…Other folates and NTD-related genes, such as methylenetetra-hydrofolate dehydrogenase (MTHFD), have not been evaluated in Brazilian population yet. Brazilian antecedents on the prevalence of the 677C>T mutation came from different populations and ethnic groups and in general, they indicated a prevalence below 10 % of TT homozygous individuals and higher prevalence of the mutation in individuals with European than African or Amerindian ancestry (Ferreira-Fernandes et al 2013;Franco et al 1998;Brandalize et al 2007;Arruda et al 1998). …”
Section: Discussionmentioning
confidence: 99%
“…The following enzymes play the key role in this process: MTHFR, MTR, MTRR, and TCN II [12,13,[21][22][23][24][25][26][27][28][29][30]. таких пациентов генетического исследования, направлен-ного на поиск тромбофилий.…”
Section: генетические предикторы прогноза при ибсunclassified
“…Methionine synthase reductase (MTRR) is a related flavoprotein that maintains the methionine synthase enzyme in an active state for the remethylation of homocysteine to methionine. A previous study demonstrated that polymorphisms in MTHFR [11], MTRR and methionine synthase (MTR) could play roles in the mechanisms predisposing for clefting, Down syndrome [12]. So far, the association between SNPs of these enzymes and folic acid status has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%